PENINGKATKAN KEMAMPUAN GURU DALAM MENETAPKAN KRITERIA KETUNTASAN MINIMAL MELALUI WORKSHOP DI SDN 7 SEMANAI - Raymansyah Raymansyah (Universitas Tanjungpura, 2022)
Teachers usually do not determine the KKM based on analysis and neither follow to the principles and steps in determining minimum Completeness criteria. Therefore, teachers need to be trained to determine minimum completeness. This study found that there was an increase in the ability ofteachers in setting minimum completeness criteria in cycle I and cycle II. Workshop activities with consultative collaborative methods provide opportunities for teachers to share experiences among themselves. Thus, understanding of the Minimum Completeness Criteria can be improved both in theory and in implementation. Therefore, it can be concluded that workshop activities can improve teacher performance in setting minimum completeness criteria at SDN 7 Semanai for the 2019/2020 academic year. The results of this study indicate that school supervisors or otherresearchers that workshop activities can be used as an alternative in improving teacher performance to determine minimum completeness criteria.